PERMASALAHAN KELUARGA EKS TENAGA KERJA WANITA DI KABUPATEN LAMPUNG SELATAN - Ruaida Murni (Puslitbangkesos Kementerian Sosial RI, 2009)
A mother who became Female Worker on one side can help a family, on the other hand raises new problems in the family. The purpose of this study is to describe the former family problems Female Worker relating to: economic factors, harmonious family and upbringing of children. The results of this study is expected to provide input and material for the relevant agencies in carnjing out the former coaching Female Worker and their families who are troubled. Type a descriptive qualitative study. Location is determined purposiv areas in the province. Lampung there is lots of ex Female Worker namely South Lampzmg Regency. The selection of informants ex Female Worker by snowballs. Collecting data through in-depth interviews, obseruation and documentation study. The results showed that the perceived problem by the family of ex Female Worker is the economic problem, which affects the disruption of family harmony, because it often appears an argument between ex Female Worker with her husband. Changing patterns of child care done by tlze former Female Worker caused friction between ex Female Worker with her husband and children. The family was happy to have gathered together, but the harmony of the family still appears troubled by frequent quarrels. The study concludes that the inability of the former family manpmver planning or female manage their business results as a Female Worker factors that cause them back through the economic slump, which triggered a fight between ex Female Worker and husband. Likewise, the imposition of changes in parenting a clzild by a former female workers, caused friction between the former child migrant workers with their husbands. It is recommended that there is coordination behveen the Directorate of Family Empowerment Ministn; of Social Affairs with the Ministn; of Manpmver and Transmigration and other related institutions, providing counseling, guidance and empowerment to prospective Female Worker and Female Worker ex and his family, so it can anticipate and help resolve family problems Female Worker ex.